Did you ever have a family - Clegg, Bill (Scout Press, 2015)
"On the eve of her daughter's wedding, June Reid's life is completely devastated when a shocking disaster takes the lives of her daughter, her daughter's fiancé, her ex-husband, and her boyfriend, Luke--her entire family, all gone in a moment. And June is the only survivor. Alone and directionless, June drives across the country, away from her small Connecticut town. In her wake, a community emerges, weaving a beautiful and surprising web of connections through shared heartbreak. From the couple running a motel on the Pacific Ocean where June eventually settles into a quiet half-life, to the wedding's caterer whose bill has been forgotten, to Luke's mother, the shattered outcast of the town--everyone touched by the tragedy is changed as truths about their near and far histories finally come to light" --